PENGARUH MEKANISME GOOD CORPORATE GOVERNANCE DAN UKURAN PERUSAHAAN TERHADAP PRAKTIK MANAJEMEN LABA (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia) - Vincentia Briganella Nevayesiana (Jurnal Ilmiah Mahasiswa FEB, 2015)
This study aims to examine the effect of the mechanisms of good corporate governance and firm size on earnings management practices. Good corporate governance mechanisms used are managerial ownership, institutional ownership, independent board, and independent audit committee. The population of the study is manufacturing companies listed in the Indonesia Stock Exchange during 2012-2014. A purposive sampling method is used to select samples and 19 companies are selected as samples. Multiple linear regression analysis using SPSS is employed as a data analysis method. The results show that institutional ownership and independent audit committee affect earnings management practices, while managerial ownership, independent board, and firm size has no effect on earnings management practices.Keywords: Good Corporate Governance, firm size, earnings management practices.